Energy providing nutrient sources - Zeyner, Anette (MTT, 2008)
Energy is the most important factor that effects exercise. It derives from different substrates used by the animal to produce a chemical intermediate that fuels all vital functions. The particular pathways and substrates that can be effectively used depend from the intensity and duration of exercise which in turn interact with the nutrient source. Energy providing nutrients are carbohydrates, fat and protein. The latter should not be primarily used for energy because this way is highly inefficient and amino acids may be needed as matter per se. Carbohydrates can be roughly subdivided into fermentable carbohydrates (f-CHO) and hydrolysable carbohydrates (h-CHO). f-CHO derive mainly from dietary fibres of roughage which can not be digested by mammalian enzymes but fermented by microbes. This occurs predominantly in the hind gut. Fibrous carbohydrates do not simply act as energy source but additionally help to maintain gut health in general and hydration during the specific situation of long-lasting strenuous exercise. h-CHO are represented by monosaccharides, disaccharides and starch that can potentially be digested by horse-own enzymes in the small intestine. However, high amounts of h-CHO may be critical concerning unfortunately elevated insulinaemic response on the one hand and disturbed hind gut fermentation on the other. Oils and fats can be substituted for h-CHO to increase dietary energy and mitigate of problems associated with starch feeding. However, fats may be problematic through inhibiting microbial fermentation. In general, energy providing nutrients have considerable side effects. To ensure gut health and for metabolic reasons it is recommended to feed no more than 0.3 kg of starchy feeds like cereal grains/kg of body weight (bwt) and day and at most 1.0 g of supplemental fat/kg bwt/day, respectively. On the other hand, 1.0 kg of roughage/kg bwt/day is the upper safe limit that needs to be ensured.
Keywords: Ko; horse; exercise; energy; protein; carbohydrates; fat